Use of technologies in healthcare: Advances and challenges (Revista Contexto & Saúde, 2025)
The advent of digital health has introduced a new paradigm in healthcare, characterized by the integration of advanced technologies into medical practice, research, and administration. Following recent reports from the Organization for Economic Co-operation and Development (OECD), four critical themes have emerged in the discourse on digital health: (1) the relationship between Artificial Intelligence (AI) and the health workforce (Almyranti et al., 2024); (2) the real value and cost of digitalization; (3) the implementation and use of electronic health records (Slawomirski et al., 2023); and (4) the collective ethical responsibility in the use of AI in healthcare (Anderson & Sutherland, 2024).
Keywords: Technologies; Healthcare